Impact of physical activity and traumatic exposure on occurrence of gestational hypertension: a survey of pregnant women in an armed-conflict region in Nigeria - Aliyu Lawan; Cecelia Apeyemi; Muhammad Chutiyami; Umar Muhammad Bello; Dauda Salihu; Buhari Abdullahi Tafida; Umar Abubakar; Adamu Ahmad Rufa'i (Taylor & Francis Group, 2020)
Objective To compare physical activity level and traumatic exposure between normotensive and hypertensive pregnant women in an armed conflict region of Nigeria. Methods 130 normotensives and hypertensive pregnant women comprising of 65 participants per group participated in the study. Harvard Trauma Questionnaire and Pregnancy Physical Activity Questionnaire were used to assess traumatic events and physical activity respectively. Results Significant difference was observed on total traumatic event (p = 0.008) and all domains and intensities of physical activity except inactivity and sedentary (p > 0.05). Household activities (OR: 0.989; 95% CI: 0.981-0.996), occupational activities (OR: 0.936; 95%CI: 0.879-0.996) and sport/exercise activities (OR: 0.898; 95%CI: 0.832-0.969) were associated with a decrease hypertensive pregnancy. Conclusion Despite exposed to traumatic events, physical activity is associated with normotensive pregnancy in an armed conflict region.